Signaling underlying kappa opioid receptor-mediated behaviors in rodents - Liu-Chen, Lee-Yuan; Huang, Peng (Frontiers in Neuroscience, 2022)
Kappa opioid receptor (KOR) agonists are potentially useful as analgesic and anti-pruritic agents and for prevention and treatment of substance use disorders. However, side effects of KOR agonists, including psychotomimesis, dysphoria, and sedation, have caused early termination of clinical trials. Understanding the signaling mechanisms underlying the beneficial therapeutic effects and the adverse side effects may help in the development of KOR agonist compounds. In this review, we summarize the current knowledge in this regard in four sections. First, studies conducted on mutant mouse lines (GRK3-/-, p38alpha MAPK-/-, -arrestin2-/-, phosphorylation-deficient KOR) are summarized. In addition, the abilities of four distinct KOR agonists, which have analgesic and anti-pruritic effects with different side effect profiles, to cause KOR phosphorylation are discussed. Second, the KOR agonist nalfurafine was the first KOR full agonist approved for clinical use and in the therapeutic dose range it did not produce significant side effects associated with typical KOR agonists. Investigations on nalfurafine, both in vitro and in vivo are reviewed. Third, large-scale high-throughput phosphoproteomic studies without a priori hypotheses have revealed that KOR-mediated side effects are associated with many signaling pathways. Lastly, several novel G protein-biased KOR agonists have been synthesized and characterized for in vitro biochemical properties and agonist biases and in vivo behavior effects. Overall, it is agreed upon that the analgesic and anti-pruritic effects of KOR agonists are mediated via G protein signaling. However, there is no consensus on the mechanisms underlying their side effects. GRK3, p38 MAPK, -arrestin2, mTOR pathway, CB1 cannabinoid receptor and protein kinase C have been implicated in one side effect or another. For drug discovery, after initial in vitro characterization, in vivo pharmacological characterizations in various behavior tests are still the most crucial steps and dose separation between beneficial therapeutic effects and adverse side effects are the critical determinant for the compounds to be moved forward for clinical development.